A Cross-Sectional Analysis of Dietary Patterns in Healthy Adolescents: Energy Balance, Nutrient Intake, Body Mass, and Serum Marker Alterations - Ștefan Adrian Martin; Roxana Maria Martin-Hadmaș (MDPI AG, 2023)
(1) Background: With shifts in daily dietary habits, concerns have arisen regarding potential impacts on metabolic health. This study sought to investigate the interplay between nutrient intake and its effects on the anthropometric and inflammatory profiles of young individuals. (2) Methods: Our approach examined the interrelation of caloric, macronutrient, and vitamin intakes with inflammatory markers, serum cholesterol, triglycerides, and other key metrics. The impact of these factors on body mass and inflammation was evaluated. (3) Results: This study found that while increased caloric intake corresponded to a rise in body fat mass, it did not significantly alter body weight, total protein, or fat profile. A dominant carbohydrate intake negatively correlated with vitamin B consumption. Interestingly, only vitamin K showcased a direct association with IL-6, while IL-8 remained unassociated with dietary intake and body mass metrics. (4) Conclusions: Dietary intake undeniably influences nutrient consumption and subsequently affects body mass metrics. Though an escalation in body fat mass was evident with increased food intake, the relationship between vitamins and inflammatory markers, based on macronutrient and caloric intake, remains inconclusive. The findings point to the potential regulatory roles of proteins and select vitamins in inflammation, emphasizing the need for deeper longitudinal studies to further validate these connections.